Use of Morgan Repertory in UTI: A Case Series - Sharma, Ruchira; Sharma, Abhishek Kumar; Mathur, Shishir (Homœopathic Links, 2019)
Background Patients with lower urinary tract infection report with unknown aetiology as a frequently encountered clinical problem.Aims To treat the patients suffering from acute symptoms of lower urinary tract infection as an add-on to standard urological care.Materials and Methods After exclusion of morphologic abnormalities, all patients with acute lower urinary tract infection who filled urinary tract infection questionnaire were offered additional homoeopathic care as an add-on to standard urological care. Standard urological care included in this study were to have adequate fluid intake to ensure the passage of 1.5 to 2 L of urine per day and maintain hygiene, especially in case of women. Symptoms were fever, incontinence, increased spasticity, decreased bladder capacity or pain, or decreased general health combined with significant bacteriuria. Seven patients were enrolled who fulfilled all the above inclusion criteria. The potencies were used according to disease grading and patient susceptibility. Descriptive statistics was used for analysis and repertory of the urinary organs and prostate gland including condylomata compiled by A.R. Morgan used for homoeopathic medicine selection.Result Seven patients were followed up for a period of 2 years. Six patients were free of urinary tract infection (UTI), whereas UTI symptoms were reduced in one patient.Conclusion Our initial experience with curing of UTI with homoeopathy according to repertory of the urinary organs and prostate gland including condylomata compiled by A.R. Morgan as add on to standard urologic care was encouraging. For an evidence-based evaluation of this concept, prospective studies are required.
Keywords: homoeopathy; urinary tract infection; A. R. Morgan repertory